Penerapan Pendekatan SAVI Dan Pendekatan Realistik dalam Meningkatkan Kemampuan Komunikasi Matematis Siswa SMP - Asmaul Husna; Rahmah Johar; Hajidin Hajidin (Jurnal Peluang, 2019)
Mathematical communication skills are very important and is one of the capabilities that should be owned by the students. To create students with good communication skills and meaningful, then used the SAVI approach and realistic approach. This study aims to determine differences in improvement of communication capabilities of students who applied mathematical SAVI approach with computer media and students who applied realistic approach in terms of the level of students' mathematical abilities. To see the interaction SAVI approach to media computer with early ability students (low, medium, and high) to the improvement of communication capabilities mathematical students, to interaction realistic approach to the initial ability of students (low, medium, and high) to the improvement of communication capabilities mathematical students , To describe the differences in the attitudes of students who applied SAVI approach with computer media and students who applied realistic approach. The population in this study were all students of class VII SMP Negeri 1 Nibong North Aceh.Samples were selected VII3 as SAVI class and the class as a class VII2 realistic. Result of analysis shows that there was no difference in improvement of communication capabilities of students who applied mathematical SAVI approach with computer media and students who applied realistic approach. There is no interaction with the computer media SAVI approach with prior knowledge of students (low, medium, and high) to increase students' mathematical communication skills. There is a realistic approach interactions with students 'initial ability (low, medium, and high) to increase students' mathematical communication skills. Students' attitudes toward learning mathematics through realistic approach has a positive attitude score higher than SAVI approach with computer media.